The causal relationship of DTI phenotypes and epilepsy: A two sample mendelian randomization study - Shang Feng; Shaobin Huang; Zhiguo Lin (Epilepsia Open)
Abstract Objective Clinical studies indicated a link between DTI imaging characteristics and epilepsy, but the causality of this connection had not been established. Therefore, we employed the Mendelian randomization analysis method to determine the causal relationship between DTI imaging characteristics and epilepsy. Method We used Mendelian randomization analysis to identify the causal relationship between brain structure and the risk of epilepsy. GWAS data of DTI phenotypes, focal epilepsy, and genetic generalized epilepsy (GGE) were utilized in the analysis. Results Our study found that DTI imaging phenotypes had a causal risk relationship with epilepsy. These phenotypes had a statistical impact on the risk of epilepsy seizures. There were differences in DTI phenotype causality between GGE and focal epilepsy, which were associated with the clinical phenotype differences of the two types of epilepsy. Significance Our study demonstrated that the diagnosis of subtypes could be assisted by comparing the differences in DTI phenotypes of specific brain regions. This meant that by studying the changes in brain regions before the onset of epilepsy, we might be able to intervene in epilepsy at an earlier stage. Plain Language Summary Our study used Mendelian randomization to explore the causal relationship between brain structure, as seen in DTI imaging, and epilepsy. We found that specific DTI phenotypes are linked to an increased risk of epilepsy seizures, with notable differences between genetic generalized epilepsy and focal epilepsy. This suggested that analyzing DTI phenotypes could help in diagnosing and potentially intervening in epilepsy earlier by finding brain changes before seizures begin.